Carnefice o spettatore? L’ingaggio spettatoriale in The Repetition. Histoire(s) du théâtre di Milo Rau - Ester Fuoco (Annali Online dell'Università di Ferrara. Sezione Lettere)
Starting from the idea that every single work of art is perceived through not only our senses but also our mind, and that the theatrical event is a privileged occasion during which the cognitive world is connected with the emotional dimension of the individual, creating an interaction between emotional experiences and critical learnings that allows for a development of the emotional intelligence, the aim of this paper is to try to describe the spectatorial engagement, prompted by the contemporary theatrical representation of the Evil. Specifically, taking as basis for the consideration the play The Repetition. Histoire(s) du théâtre, first chapter of the series Histoire(s) du théâtre dedicated to the theatrical essence – the tragedy, in this case – of Milo Rau.